2004
DOI: 10.1080/01677060490500294
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and Stroke in a Population From Eastern Turkey

Abstract: Human apolipoprotein E (apo E) alleles are polymorphic with significantly different frequencies among different ethnic groups and have been associated with increased risk of coronary heart disease, and postulated as a major genetic susceptibility locus for Alzheimer's disease. Studies undertaken in different populations have shown different association patterns between apo E genotype and stroke. The aim of this study was to determine the risk of apo E genotype in stroke patients living in the eastern part of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(45 reference statements)
0
8
2
1
Order By: Relevance
“…We were unable to determine any association between the apoE alleles and AS in Turkish patients, as in another study from the east of Turkey [12]. However, assessment of the Hardy-Weinberg equilibrium for genotypes among controls revealed significant deviation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We were unable to determine any association between the apoE alleles and AS in Turkish patients, as in another study from the east of Turkey [12]. However, assessment of the Hardy-Weinberg equilibrium for genotypes among controls revealed significant deviation.…”
Section: Discussioncontrasting
confidence: 53%
“…Few studies have investigated apoE polymorphism in the Turkish population with stroke [12]. It was previously determined that apoE polymorphism could alter serum lipid levels, but possible alteration in Lp(a) levels in stroke patients due to apoE polymorphism has not been investigated before.…”
Section: Introductionmentioning
confidence: 98%
“…Szolnoki and colleagues [29] also found that the presence of e4 acted synergistically with hypertension, smoking, diabetes and drinking in both large and small-vessel ischaemic stroke. However, recent studies have also showed no association [30][31][32][33].…”
Section: Apolipoprotein E (Apoe)mentioning
confidence: 91%
“…Clearly, until further studies have E4 and smoking with stroke [28,29] No association [30][31][32][33] No association [34,35] No association with CADASIL T with stroke [57 ,58 ] No association [55,56] T with smoking and stroke [29] Factor V Leiden R506Q 0.05…”
Section: Il-6mentioning
confidence: 99%
“…Studies on the relation between the ApoE gene ε4 polymorphism (ApoE/4) and cerebral infarction have given conflicting results. Several population-based studies, in Italy [5], Turkey [6] and Taiwan [7] have shown no association between ApoE/4 and stroke. A study in China, however, showed a 2.1-fold significantly increased risk of cerebral infarction in ApoE/4 carriers [8].…”
Section: Apolipoprotein E Genementioning
confidence: 97%